A New Orleans Author in Mark Twain's Court : Letters from Grace King's New England Sojourns - King, Grace Elizabeth, 1851 or 1852-1932 (Book collections on Project MUSE., 2019)
"Shortly after Grace King wrote her first stories in post-Reconstruction New Orleans, she entered a world of famous figures and literary giants greater than she could ever have imagined. Notable writers and publishers of the Northeast bolstered her career, and she began a decades-long friendship with Mark Twain and his family that was as unlikely as it was remarkable. Beginning in 1887, King paid long visits to the homes of friends and associates in New England and benefited from their extended circles. She interacted with her mentor, Charles Dudley Warner; writers Harriet Beecher Stowe and William Dean Howells; painter Frederic E. Church; suffragist Isabella Beecher Hooker; Chaucer scholar Thomas Lounsbury; impresario Augustin Daly; actor Will Gillette; cleric Joseph Twichell; and other stars of the era"--